The effects of diagenetic overprint processes on the mineralogy and ultrastructure of biogenic calcium carbonates - Mages, Viola Julia (Ludwig-Maximilians-Universität München, 2021)
This dissertation´s research is part of the DFG funded working group named CHARON, which is running since 2013, encompassing two phases with this work being part of the second phase. The aim of the CHARON working group is the collection of an extensive and diverse information pool on the diagenesis of calcium carbonates. The general goal was to make palaeoenvironmental reconstructions more precise and reliable. The role of this subproject was the in-depth investigation of the individual steps of the diagenetic overprint process on calcium carbonate skeletal parts of biogenic origin. Along with XRD and AFM analyses, the most important method was electron backscatter diffraction (EBSD) coupled with scanning electron microscopy (SEM). This way comprehensive results on ultrastructure, mineralogy, crystallography, and textural features like the porosity, and the ultrastructure along with their alteration during diagenesis or the experimental hydrothermal treatments, respectively, were compiled. For this, fossil material was utilized, as well as material which has been hydrothermally treated in a laboratory setting. The fossil material consisted of brachiopods from the extinct taxa Afghanospirifer sp., Alispirifer middlemissi, Gigantoproductus sp., Gypospirifer sp., Hunzina electa, Terebratula scillae, Tetractinella trigonella, Trigonotreta larghii, and Trigonotreta lyonsensis. The fossils originated from four geological basins: the Castell’Arquato Basin in northern Italy with a thermal gradient of up to 50 °C, the Pennine Basin in central northern England with a thermal gradient between 100 and 120 °C, the Lombardian Basin in northern Italy with a thermal gradient ranging from 150 to 200 °C, and the complex Karakoram Basin in the very north-east of Pakistan with a thermal gradient between 300 and 350 °C. The recent materials that were utilized for the hydrothermal experiments were various extant marine organisms: the bivalves (mussels) Aequipecten opercularis, Arctica islandica, and Mytilus edulis, the sea snail Haliotis ovina, and the stony coral Porites sp. Additionally, aragonitic as well as calcitic inorganic monocrystals were employed in the experiments. The experimental setup comprised one temperature of 175 °C, two alteration fluids: burial and meteoric, four time spans ranging from 4 to 28 days (pristine and, where available, fossil material has also been investigated), and the five different materials mentioned above. Results from the naturally and laboratory altered samples reveal that the overprint process proceeds along a specific line of events, but presents small variances in the strength of the individual characteristics. All samples showed the sequence of 1) loss of the organic matter leading to the formation of secondary porosity, enhancing the overall porosity, as well as mechanical disintegration along textural features, 2) amalgamation of singular ultrastructural units into larger clusters by merging and the adaptation of one common orientation, leading to the distortion of the characteristic shapes of the ultrastructural units into more rounded shapes while maintaining the existing mineralogy, and 3) nucleation of secondary calcite grains in the open cavital space and, with ongoing growth, the substitution of the pre-existing ultrastructure and mineralogy by secondary calcite. The factors influencing the rapidity and strength of an overprint were determined and isolated. The external ones are the obvious ones, such as 1) the temperature or geothermal gradient. This naturally presents a positive correlation to the level of overprint. That means, the higher the temperature, the stronger the overprint. The same holds true for 2) the duration of the influence and the prevailing 3) pressure conditions: the longer the duration and the higher the pressure, the stronger the overprint. 4) The alteration fluid, through its contained inhibitors, influences the intensity of the dissolution and reprecipitation of the mineral matter. The influence of the internal factors is more complex. 5) The ultrastructure determines the amount and distribution of the organic matter as well as the mineralogy and interfacial energy. 6) The organic matter, through its disintegration, forms the network of the interconnected secondary porosity and determines the extent of the cavital space. 7) The porosity enables the percolation of the alteration fluid and presents open space for the nucleation of secondary calcite. 8) The mineralogy defines the solubility of the material and influences the extent and kinetics of the dissolution. This research lies in the field of palaeoenvironmental reconstruction. This is primarily done with the aid of geochemical proxy carriers, such as the calcium carbonatic skeletal parts of the marine invertebrates investigated in this work. Such a geochemical proxy would, for example, be the oxygen isotopes. Measuring the ratio of the heavy 18O isotope to the light 16O isotope gives information on how much cryosphere, meaning ice matter, has been present at the time of life of the animal used for this hypothetical investigation. It is a common occurrence that during the formation of biogenic minerals, these minerals do not form in accordance with the environmental conditions surrounding the animal. This is made possible, because some animals can influence the conditions in the areas of growth at a small scale, so that phases that are metastable or instable can form regardless. This can only be upheld during the lifetime of the organism. But after the death of the organism, its sedimentation and through diagenesis comes an alteration of the skeletal hard parts. As will be shown in this dissertation, this alteration encompasses various processes of dissolution and reprecipitation. This leads to the ablation of primary, original matter and the addition of secondary, new material. With that the primary isotopes are exchanged by secondary isotopes and the measurements do not represent the isotopic signature of the time of life of the organism any more. As marine carbonates are most commonly used for palaeoenvironmental reconstructions, the findings of this research can, for example, be used to determine if and to which level the material at hand has been altered. The detailed investigations allow to pinpoint all specific occurrences individually for each area or ultrastructure. Furthermore, the specific reactions and susceptibilities of the various ultrastructures to develop certain features were worked out. These and further findings of this work allow to assess the suitability of the general material as well as specific areas of it as a geochemical proxy carrier.